Investigating Antibiotic Effects on Trichoderma sp. Growth and Virulence: A Basis for CRISPR-Cas9 Preparation - Purnomo Hari; Wafa Ali; Hasanah Himmatul; Nawangsari Putri; Megasari Dita; Wardhana April Hari; Khoiri Syaiful (BIO Web of Conferences)
Trichoderma sp. is an antagonistic fungus that is used as a biological control. Understanding how antibiotics affect Trichoderma sp. growth and virulence is critical for developing effective CRISPR-Cas9 gene editing strategies. However, implementing CRISPR-Cas9 technology in Trichoderma requires a comprehensive understanding of how external factors, such as antibiotic exposure, affect the fungus’s growth and virulence over successive generations. Antibiotics long-term effects on fungal physiology remain unclear. This study addresses this gap by evaluating the impact of antibiotic treatment on Trichoderma sp., laying the groundwork for effective and precise genetic modifications using CRISPR-Cas9. Five types of antibiotics used for this test are Chloramphenicol, Gentamicin sulphate, Kanamycin Meiji, Penicillin Meiji, and Tetracycline HCI. The study found that several antibiotics accelerated the growth of Trichoderma sp., allowing the fungus to fill a petri dish in under 5 days. However, this rapid growth was delayed in subcultures over five generations. Although the color of the fungus did not vary much across treatments, subtle changes in density and brightness were detected in each generation using the "color grab" application, with these attributes diminishing over time. Spore density in the fourth generation, particularly under chloramphenicol and gentamicin treatments, differed from other antibiotics. Germination rates were initially high (≥70%) but decreased with each generation. The fungus maintained strong virulence against Fusarium sp., with inhibition rates ≥50%, and exhibited mycoparasitism, characterized by hyphal growth at the Fusarium sp. colony edges. This research contributes to understanding how antibiotic exposure affects the long-term growth, spore density, and virulence of Trichoderma sp., providing essential insights for optimizing its use in biocontrol and genetic engineering applications.